The Nature and Causes of Profits: The Classical Approach from Smith to Marx - Sean Kimpton (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2014)
The Global Financial Crises has motivated some to rethink the dominance of global capitalism. This has revived an interest in Marxist doctrine and in particular its examination of the notion of exploitation. Marx's theory of value is central to his examination of exploitation. This paper will show that both these posits of Marx are in error. Further, it will show that Marx draws heavily on Smith's idea of the primacy of wages. However, this paper will demonstrate that profit, and not wages, are the original source of income. This paper reaffirms the importance of profits and the ability of entrepreneurs and capitalists to pursue them.
Keywords: 330; Adam Smith; Karl Marx; Profit; Exploitation; Labour Theory of Value; Classical Economics